The Relationship Between Use Of 3 Monthly Contraceptive Injection And Menstrual Disorders At Gloria Clinic - Kristiyani, Winda; Simarmata, Mesrida; Anugerah Laia, Boy (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Introduction : Density population has a great influence on welfare and health population . Contraception is tools used​ in prevent the occurrence pregnancy.In​ election usage tool contraception can varies However own advantages and disadvantages of each method contraception. Purpose : To analyze long term relationship 3 month birth control injection with disturbance cycle menstruation Method : Research design survey analytics , with approach cross sectional, namely try dig how and why phenomenon That occurred . Population and Sample: all 3- monthly injectable birth control acceptors who experienced and did not experience experience disturbance at the time menstruation totaling 30 acceptors , the total sampling is then sample a total of 30 acceptors . Place and time : at the Gloria Clinic, Teluk Dalam Market, Teluk Dalam District , South Nias Regency, North Sumatra Province , April -June 2024. Results : Based on The results of the Chi-Square statistical test P= 0.000 (<0.05) that There is Relationship between the duration of use of 3 - month injectable contraceptives and Disturbance Menstruation In Acceptors 3 Months Injectable Birth Control In Di Gloria Clinic, Teluk Dalam Market , Teluk Dalam District, South Nias Regency, North Sumatra Province , 2024 Conclusion : There is a relationship between the length of use 3 month birth control injection with disturbance cycle menstruation